Career development at rural library: an analysis towards stigma of needs and challenges / Nor Azlina Azmi, Haziah Sa'ari and Raja Alwi Raja Omar - Azmi, Nor Azlina; Sa'ari, Haziah; Raja Omar, Raja Alwi (2013)
Rural library in Malaysia plays an important role in delivering services that meet the information needs of rural area residents and as an intermediary between the resources and the user's demand for knowledge. Rural libraries are at a critical point whereby they become provider for Lifelong Learning and also act as catalysts that rejuvenate and connect their communities. Their existence signifies government earnestness to eliminate any assumption that the rural communities are isolated or ignored compared to the urban community. Library Officers and the supporting staff in rural libraries who are in-charged with supporting rural library services are important human capital. Their responsibility is a challenging one as they have to serve the small towns and rural areas across the country, far from the luxuries of the cities and with majority of rural libraries having insufficient staff. The objective of the research is to study the training needs of the Library Assistants and to investigate the challenges face by the Library Assistants in carrying out their duties at rural libraries. A survey questionnaire was use to obtained data. Questionnaires were distributed to 120 respondents who Library Assistant are attending the basic library course organized by the Faculty of Information Management, Universiti Teknologi MARA (UiTM) Puncak Alam and the National Library of Malaysia. Data was analyzed by descriptive statistic method. The findings indicated that the respondent needed and preferred training on basic library operation to ensure they could carry the daily tasks effectively and efficiently. The second training that is important to be given is courses on library activities. The respondents also indicated that job insecurity f improper planning of library activities and the ignorance of the rural community on the function of library as the challenges faced by them.